Growth and gas exchange of soursop under salt stress and hydrogen peroxide application - Veloso, Luana L. de S. A.; Silva, André A. R. da; Lima, Geovani S. de; Azevedo, Carlos A. V. de; Gheyi, Hans R.; Moreira, Rômulo C. L. (Revista brasileira de engenharia agrícola e ambiental, 2022)
ABSTRACT The cultivation of irrigated soursop in semiarid Northeastern Brazil highlights the need for information regarding its responses to the salinity of irrigation water and the use of techniques that allow its exploration, such as the use of hydrogen peroxide. Thus, the study aimed to evaluate the effect of soaking of seeds and foliar application of hydrogen peroxide on soursop plant growth and physiology under conditions of salt stress. The study was conducted in lysimeters in a greenhouse, and the treatments were distributed in a randomized block design and 4 × 4 factorial scheme, with four values of electrical conductivity of the irrigation water - ECw (0.7, 1.7, 2.7, and 3.7 dS m-1) and four concentrations of H2O2 (0, 25, 50, and 75 μM), with three replicates and one plant per plot. H2O2 concentrations were applied via seed imbibition and foliar spray. Irrigation with water from 0.7 dS m-1 impairs gas exchange and absolute growth rates of plant height and stem diameter and relative growth rate in height of soursop plants. Concentrations of 35, 33 and 23 µM of hydrogen peroxide favored the relative and absolute growth rates of plant height and transpiration, respectively. Compared to the aerial part, the root of soursop plants is more affected when irrigated with water from 1.6 dS m-1. RESUMO O cultivo da graviola irrigada no semiárido do Nordeste brasileiro evidencia a necessidade de informações sobre suas respostas à salinidade da água de irrigação e o uso de técnicas que permitam sua exploração, como a utilização de peróxido de hidrogênio. Assim, objetivou-se com este estudo avaliar efeitos de embebição e aplicações foliares de peróxido de hidrogênio sobre o crescimento e a fisiologia de gravioleiras submetidas à estresse salino. O estudo foi conduzido em lisímetros em casa de vegetação, e os tratamentos foram distribuídos no delineamento de blocos casualizados em esquema fatorial 4 × 4, com quatro valores de condutividade elétrica da água de irrigação - CEa (0,7; 1,7; 2,7 e 3,7 dS m-1) e quatro concentrações de H2O2 (0, 25, 50 e 75 μM), com três repetições e uma planta por parcela. As concentrações de H2O2 foram aplicadas via embebição das sementes e pulverização foliar. A irrigação com água a partir de 0,7 dS m-1 prejudicou as trocas gasosas e as taxas de crescimento absoluto da altura de planta e diâmetro de caule e crescimento relativo da altura de gravioleira. A aplicacão foliar com concentrações estimadas de 35, 33 e 23 µM de peróxido de hidrogênio favoreceram as taxas de crescimento relativo e absoluto da altura de plantas e transpiração, respectivamente. Em comparação com a parte aérea, a raiz de gravioleira foi mais afetada quando irrigadas com água a partir de 1.6 dS m-1.